Implementation of Value Stream Mapping for Waste Reduction in Crude Palm Oil Production Process - Meutia Fadilla; M. Dirhamsyah, M. Dirhamsyah; Husni, Husni (AGUSPATI Research Institute, 2021)
PT. Perkebunan Nusantara I Cot Girek is one of the palm oil mills owned by PT. Perkebunan Nusantara I which is engaged in processing palm oil into Crude Palm Oil and Palm Kernel Oil. The problem faced by PTPN I Cot Girek Unit is that there are several wasteful activities that cause the company to experience time losses, production does not reach targets and quality damage to Fresh Fruit Bunch (FFB) and Coconut Palm Oil (CPO). The problem solving method used are Value Stream Mapping to identify wasteful activities, the 5W1H method to identify the causes of waste and the Weighted Product Method to determine the order of priority for improvement. Based on the results of the study, there are 4 activities that can be taken corrective action. After being analyzed using VSM, it was found that the Manufacturing Lead Time decreased from 1185.70 minutes to 1069.73 minutes and the Process Cycle Efficiency value increased from 67% to 74%.